Common menstrual disorders in adolescent girls attending a tertiary care center - P., Hibina K.; K., Nishi Roshini; A., Andrews M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Menstrual disorders are an important cause of concern among adolescent girls. Most problems are physiological but few have underlying pathology which has adverse effect on the future reproductive health Aim of the study was to know the prevalence and to evaluate the underlying cause of the menstrual problems in adolescent girls seeking medical care. Methods: This is a cross sectional study conducted in in 215 adolescent girls aged 13-19 years who sought medical care over a period of 12 months for menstrual complaints from the department of obstetrics and gynecology, Govt. Medical College, Thrissur, a tertiary care center in middle of Kerala, South India. Data was analyzed by SPSS software and p value <0.05 was taken statistically significant. Results: Dysmenorrhea was the most common problem (57.5%), followed by scanty menstruation (35.35%) and 25.2% of girls suffered from premenstrual symptoms. Hypothyroidism was seen in 2.4% of girls 40% were anemic. Statistically significant association was found between hypothyroidism and features of hyperandrogenemia with cycle irregularity. Ultrasonographic evidence of polycystic ovarian morphology was identified among 61.9% girls with irregular cycles. Conclusions: Even though majority of menstrual issues are self-limiting proper evaluation and follow up for medical disorders like hypothyroidism and anemia are important and appropriate intervention is crucial for future reproductive and general health of adolescents presenting with Menstrual disorders.